Economic Announcements and the Timing of Public Debt Auctions - Rossi, Marco (International Monetary Fund, 1998)
Most treasuries around the world sell their securities at auctions either directly or indirectly through an agent, usually the central bank. Although they can control both the rules and the timing of the auction, they may not be able to control the information and valuations of bidders. The purpose of this paper is to identify those economic indicators whose announcement is likely to have a significant impact on government securities prices and, hence, on bidders' behavior at auctions of government securities. This information could be used to schedule treasury securities auctions so as to minimize public debt management costs